Solve each given equation and show your work. Tell whether it has one solution, an infinite number of solutions, or no solutions, and identify each equation as an identity, a contraction or neither.
A) 20-4x=12-x+8-3x
B) 5x+4x-3+24+8x
C) 5x +6+2x+6+3x-15
Confusing please help
These are three equations and three answers.
Answers:
A) infinite solutions, identityB) one solution, x = 27, neither contradiction nor identiyC) x = no solutions, contradictionExplanation:
Equation A: 20 - 4x = 12 - x + 8 - 3x
The objective is clearing the unknown, which is to isolate it in one side of the equation.
These are the steps and properties that you need to use:
1. Combine like terms on right side:
20 - 4x = 20 - 4x
2. Use addition property of equality (add 4x on each side).
20 = 20 ↔ identity
Conclusion: you have gotten a condition that is always true, no matter the value of x, which means that the equation has infinite solutions and it is an identity.
Equation B: 5x + 4x - 3 = 24 + 8x (note that I placed the equal sign as it was missing)
1. Combine like terms on each side:
9x - 3 = 24 + 8x
2. Subtraction property and addition propertiy of equality (subtract 8x and add + 3 on both sides)
x = 27 ↔ solution (neither contradiction nor identity)
Conclusion: the solution is x = 27.
Equation C: 5x + 6 = 2x + 6 + 3x - 15 (note that I placed the equal signs as it was missing)
1. Comitne like terms on the right side:
5x + 6 = 5x - 9
2. Subtraction property of equality (subtract 5x from each side)
6 = - 9 ↔ contradiction
Conclusion: the equation does not have a solution since the final equality is always false (a condradiction or absurd).
For your information, when the variable (x) dissapears and fhe final equality is always true (for example 0 = 0, or 20 = 20), the equation is an identity.
A) 20-4x=12-x+8-3x
Bring all x values at one side and all numerical values to the other side of the equal sign and solve. Also, do not forget to change the sign when you change the side.
-4x + x + 3x = -20 + 12 + 8
-4x + 4x = -20 + 20
0 =0 No solution
B) 5x+4x-3+24+8x
this expression can only be simplified to 17x + 21 and not solved because there is no equal sign here
C) 5x +6+2x+6+3x-15
this expression can only be simplified to 10x - 3 and not solved because there is no equal sign here
Also, neither of these is an identity or contraction.
please answer this i dont understnad
Please Help ASAP 20 points
Find the slope of the line through the given points.
(−1, 2) and (−5,10)
(1,3) and (0,−9)
(18, 6) and (−7, 7)
(−7, 10 ) and (1, 10)
Pls help will mark brainliest
4x+2y=6
x-3y=5
SOLVE BY ELIMINATION METHOD PLS
Answer:
y=-1
Step-by-step explanation:
The first step to solving this problem is to write it out like this-->
4x+2y=6
x-3y=5
Next you want to eliminate the X's or the Y's, I chose to elininate the X's-->
4x+2y=6
-4(x-3y=5) [You MUST distribute the -4 to each of the numbers in the equation]
Then you get--->
4x+2y=6
-4x+12y=-20 Then you add them top to bottom--->
0x+14y=-14 [At this point you dont have to write the X]Next you solve for y-->
14y=-14 Divide both sides by 14, in order to get the y by itself-->
y=-1 And theres your answer hope it helps :D
we have the 2 equations
4x + 2y = 6 → (1)
x - 3y = 5 → (2)
multiply (2) by 4
4x - 12y = 20 → (3)
(3) - (1) to eliminate the terms in x
- 14y = 14 ( divide both sides by - 14 )
y = - 1
substitute y = - 1 into (1) and solve for x
4x - 2 = 6 ) add 2 to both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is x = 2, y = - 1
I just need help on learning how to do ten and eleven thank you!
Anyone good with Literal Expressions?
Answer:
[tex]\boxed{F=\dfrac{9}{5}c+32}[/tex]
Step-by-step explanation:
[tex]\dfrac{5(F-32)}{9}=c\qquad\text{multiply both sides by 9}\\\\5(F-32)=9c\qquad\text{divide both sides by 5}\\\\F-32=\dfrac{9}{5}c\qquad\text{add 32 to both sides}\\\\\boxed{F=\dfrac{9}{5}c+32}[/tex]
1000m divided by 100n can be written in the form 10z. Express z in terms of m and n
Answer:
[tex]10 ^ {3m-2n} = 10 ^ z[/tex]
Where z = 3m-2n
Step-by-step explanation:
An important mathematical property about the powers is that when powers of equal base are divided, the same base is placed and the exponents are subtracted.
Then we can write 1000m and 100n as powers of the same base:
[tex]1000 ^ m = (10 ^ 3) ^ m = 10 ^ {3m}\\ 100 ^ n = (10 ^ 2) ^ n = 10 ^ {2n}[/tex]
Now we perform the division of powers of the same base (10)
[tex]\frac{10 ^ {3m}}{10 ^ {2n}} = 10 ^ {3m-2n}[/tex]
Finally
[tex]10 ^ {3m-2n} = 10 ^ z[/tex]
Where z = 3m-2n
To express z in terms of m and n, rewrite the equation: 1000m / 100n = 10z. Then, simplify to 100m / 10n = z. So, z can be expressed as 10m/n.
Explanation:The given equation is 1000m divided by 100n equals to 10z. To express z in terms of m and n, we need to isolate z. Let's proceed step by step:
First, rewrite the equation: 1000m / 100n = 10z;Then, eliminate the 10 on the right side by dividing both sides by 10, we get: 100m / 10n = z; Then, simplify the left side, we get: 10m/n = z;So, z can be expressed as 10m/n.
Learn more about Algebraic Expression here:https://brainly.com/question/953809
#SPJ2
P = 215 (1.005)t/3 the equation above can be used to model the population, in thousands, of a certain city t years after 2000. according to the model, the population is predicted to increase by 0.5% every n months. what is the value of n
As t/3 it means that 0.5% every 3 years.
So n will be 3 years , 36 months
Solution:
The Given model to Predict the population
[tex]P=P_{0}(1.005)^{\frac{t}{3}[/tex]
----------------------------------(1)
The population increases by 0.5 % every n months.
Initial Population = 215
Final Population
[tex]=215+215\times \frac{0.5}{100}\\\\=215+1.075\\\\=216.075[/tex]
Substituting the value of , Initial and final Population in equation 1,
[tex]216.075=215\times (1.005)^{\frac{t}{3}}\\\\ (1.005)^{\frac{t}{3}}=\frac{216.075}{215}\\\\ (1.005)^{\frac{t}{3}}=(1.005)^{1}\\\\ \frac{t}{3}=1\\\\ t=3[/tex]
t=3 years =36 months
The value of n is equal to 36 months.
X+3x-2=6x-12 please help
If i leave my house at 6:52 am and run 1 mile at an easy pace (8:15 per mile), then 3 miles at tempo (7:12 per mile) and 1 mile at easy pace again, what time do i get home for breakfast?
Running 2 miles at 8:15 per mile takes 16:30 minutes.
Running 3 miles at 7:12 per mile takes 21:36 minutes.
The total running time is 16:30 + 21:36 = 38:06 minutes. That length of time after 6:52 am is 7:30:06 am.
You get home for breakfast at 6 seconds past 7:30 am.
By adding the times spent on each individual run to your start time, you should arrive home at approximately 7:30 am.
Explanation:To begin with, this is a question about time calculation, where you need to know exactly how to calculate time durations. First, you start running at 6:52 am. Your easy pace is 8 minutes 15 seconds, or 8.25 minutes, per mile and you do this once before and once after your tempo run. So, for 2 miles, it's 2*8.25 = 16.5 minutes.
Then you have a tempo pace at 7 minutes 12 seconds, or 7.2 minutes, per mile. You run 3 miles at tempo pace, so that's 3*7.2 = 21.6 minutes.
Adding these two results together, you have a total running time of 38.1 minutes (16.5 minutes easy pace + 21.6 minutes tempo pace). Adding this to your start time of 6:52 am gives you a rough end time of 7:30 am. Please note that this estimation rounds your running time to the nearest minute.
Learn more about time calculation here:https://brainly.com/question/34080240
#SPJ2
need help finding the x, y, and z. please and thank you
The first step in any problem is to look at what you are given. When solving systems of linear equations, it is often helpful to eliminate one or more of the variables by adding or subtracting a multiple of one equation with a multiple of another. It is convenient when at least one of the multipliers is 1.
Here, we can cancel the y-terms in the 2nd and 3rd equations simply by adding them together. This gives
... (5x +y -4z) +(-3x -y +5z) = (41) +(-45)
... 2x +z = -4 . . . . simplified
Likewise, we can add 3 times the second equation to the first to cancel y in that sum.
... 3(5x +y -4z) +(2x -3y +z) = 3(41) + (-1)
...15x +3y -12z +2x -3y +z = 123 -1
...17x -11z = 122 . . . . simplified
Now that we have 2 equations in x and z, we can go through the same process. We observe that the coefficient of z is +1 in the first equation and -11 in the second. The means we can cancel the z terms by adding 11 times the first equation to the second:
... 11(2x +z) +(17x -11z) = 11(-4) +122
...22x +17x = 78 . . . . . . simplify a little bit
... x = 78/39 = 2 . . . . . . divide by 39
From above, we find
... z = -4 -2x = -4 -2·2 = -8
... y = 41 -5x +4z = 41-5(2) +4(-8) = 41 -42 = -1
The solution is (x, y, z) = (2, -1, -8).
_____
The method of elimination used here will vary with the system of equations. If you want to employ a consistent method, you can use Cramer's Rule, Gaussian elimination, or matrix methods. Since you apparently don't mind help from technology, learning to do this on your graphing calculator can also be a good idea.
Write the equation of the line parallel to the given line and passing through the given point.
y=2x−8 through (3,10)
Copy down y = 2x - 8. Note that any line parallel to this will have exactly the same form, although the constant (representing the y-intercept) may be different.
Knowing that this line passes through (3,10), all we have to do is find the value of the constant of this new, parallel line. Substitute 10 for y and 3 for x, obtaining 10 = 2(3) + b. Then 10-6 = b, or b = 4, and:
y =2x + 4 (answer). Again, note how the form of this new equation is exactly the same as the form of the given equation; only the constant (the y-intercept) is different.
Answer:
y=2x+4
Step-by-step explanation:
The equation we have is y=2x-8, so we subsitute the values and 8 is equal to b. After you substitue you solve it. b=4. So, the answer is y=2x+4
Hope this helped :) *also sorry if I spelled some words wrong*
Can anyone transform a vertex form equation into a standard form?
y= -0.3(x-0)^2+3
If you can show work.
the standard form of a quadratic is : y = ax² + bx + c : (a ≠ 0 )
note that (x - 0 )² = x²
distributing by - 0.3 gives
y= - 0.3x² + 3 ← in standard form
with a = - 0.3, b = 0 and c = 3
Which ordered pairs are solutions to the inequality −2x+y≥−4 ?
Select each correct answer.
(0, −5)
(3, −1)
(1, −2)
(0, 1)
(−1, 1)
Answer:
(0,-5) , (1,-2) , (0,1) and (-1,1)
Step-by-step explanation:
-2x + y ≥ -4
y ≥ 2x - 4
Taking a point (0,-5):
-5 ≥ 0 - 4 , 5 ≥ -4
This situation is true.
Taking a point (3,-1):
-1 ≥ 2(3) - 4 , -1 ≥ 2
This situation is not true.
Taking a situation (1,-2):
-2 ≥ 2(1) - 4 , -2 ≥ -2
This situation is true.
Taking a point (0,1):
1 ≥ 0 - 4 , 1 ≥ -4
This situation is true.
Taking a point (-1,1):
1 ≥ 2(-1) - 4 , 1 ≥ -6
This situation is true.
The correct answers are
(−1, −1)
(5, −12)
(0, 1)
Have a nice day!
72 ÷(11-3²) ÷ 3 but as a fraction
Let's evaluate the quantity within the parentheses. (11 - 3^2) becomes (2). Then we have:
(72 divided by 2) / 3, or 36/3, or 12.
A number, n, is multiplied by -3/8. The product is -0.1. What is the value of n?
Rewriting this symbolically, (-3/8)n = -0.1. Let's solve for n. To do this, multiply both sides of the equation by (-8/3). This results in n = 8/30, or n= 4/15.
Select the functions that have a value of -1. sin180° cos180° tan180° csc180° sec180° cot180°
We have to break each degree in terms of 90
A) [tex]sin180^\circ=sin(90\times2+0)[/tex]
Which is in third quadrant, therefore sine is negative hence
[tex]sin(90\times2+0)= -sin0 ^\circ = 0[/tex]
B) [tex]cos180^\circ =cos(90\times2+0)[/tex]
Which is in third quadrant, therefore cosine is negative hence
[tex]cos(90\times2+0)= -cos0^\circ = -1 [/tex]
C) [tex] tan180^\circ=tan(90\times2+0)[/tex]
Which is in third quadrant, therefore tangent is positive hence
[tex]tan(90\times2+0)= tan0^\circ = 0[/tex]
D) [tex]csc180^\circ=csc(90\times2+0)[/tex]
Which is in third quadrant, therefore cosec is negative hence
[tex]cosec(90\times2+0)= -csc0^\circ =[/tex]not defined
E)[tex]sec180^\circ=sec(90\times2+0)[/tex]
Which is in third quadrant, therefore secant is negative hence
[tex]sec(90\times2+0)= -sec0^\circ = -1 [/tex]
F) [tex] cot180^\circ=cot(90\times2+0)[/tex]
Which is in third quadrant, therefore tangent is positive hence
[tex]cot(90\times2+0)= cot0^\circ = [/tex] not defined
Hence only [tex] cos 180^\circ [/tex] and
[tex] sec180^\circ [/tex] have value -1
Hope this will help
Answer:
Cos and Sec
Step-by-step explanation:
thats the short of the guy above
when multipling signed numbers how do you know wether the number is positive or neagitive
If an odd number of minus signs are involved in a product or quotient, the sign of the result is negative. Otherwise, it is positive.
Examples:
(-1)(-1) = 1
(-1)(-1)(-1) = -1
(-1)/(-1) = 1
(-1)(-1)/(-1) = -1
The product of two positive numbers is positive: (+)(+) = (+).
The product of one positive number and one neg number is neg: (+)(-) = (-).
The product of two negative numbers is positive: (-)(-) = (+)
Solve the problem using the previous balance method.
The account balance on April 1st is $60.15.
On April 15th a payment of $51.00 is made.
On April 25th a purchase of $91.27 is made.
What is the finance charge if the annual rate is 18%?
What is the new account balance?
Finance charge = $ ____
New balance = $ ____
Annual Percent Rate (APR) = 18%
Rate during the current billing cycle = 18/12 = 1.5%
Balance at the beginning of the billing cycle = 60.15
Payment 51.00
Balance 10.15
Purchase 91.27
Balance - 81.12
Finance Charge 60.15 * 0.015 = 0.90
New Balance - 82.02
To get the color dove-white, Ken mixed black paint and white paint in a ratio of 5:3. He used 20 gallons of black paint. How much white paint did he use?
12 gallons of white paint
divide 20 gallons by 5 to obtain 1 part of the ratio
[tex]\frac{20}{5}[/tex] = 4 gallons ← 1 part
white paint = 3 × 4 = 12 gallons ← 3 parts
Graph f(x)=12x+2.
Use the line tool and select two points to graph the line.
Answer:
(0,2) and (1,14)
Graph is attached.
Step-by-step explanation:
Let us find y intercept
When x=0, y = f(x) =2
Hence one point is (0,2)
Other point is let x = 1,
y =12(1)+2 =14
(1,14) (0,2) are plotted and joined.
Graph is attached.
I need help with this one please help asap thank you
there are 200 students in the 7th grade 98% of the students in the greater going on the field trip how many students are going on the field trip show your work and I will mark brainiest
30 percent
22% of 200 is 44, 44 students play football
12 of 200 is 24, 24 students play baseball
44+24=68
The teams have a total of 68 players
because 8 play both sports you subract 8
68-8=60
The answer is a tolal of 60 students play sports
I think the answer is 60
What is the value of the expression (9+15) divided by 3 plus 2
Hey!
This question is super easy to me. This question is going to be used their order of operations.
Order of operations stands for
↓
P-Parenthesis
E-Exponents
M-Multiply
D-Divide
A-Add
S-Subtract
(9+15)/3+2
24/3+2
8+2
=10
Answer⇒⇒⇒⇒⇒=10
Hope this helps!
Thank you for posting your question at here on Brainly.
-Charlie
Answer:
10
Step-by-step explanation:
(9+15) ÷ 3 + 2 = 10
How many subsets of 100 have exactly 99 elements?
How many subsets of 100 have exactly 98 elements?
How many subsets of 100 have exactly 2 elements?
The number of k-element subsets of a set of n elements is given by
... C(n, k) = n!/(k!(n-k)!)
a) C(100, 99) = 100!/(99!×1!) = 100
b) C(100, 98) = 100!/(98!×2!) = 100*99/2 = 4950
c) C(100, 2) = 100!/(2!×98!) = 4950 . . . . same as (b)
Use the identity x^3+y^3+z^3−3xyz=(x+y+z)(x^2+y^2+z^2−x^y−y^z−z^x) to determine the value of the sum of three integers given:
the sum of their squares is 110,
the sum of their cubes is 684,
the product of the three integers is 210,
and the sum of any two products (xy+yz+zx) is 107.
Correctly written, your identity would tell you ...
... (sum of cubes) - 3·(product) = (sum of integers)·((sum of squares) - (sum of any two products))
Filling in the given numbers, you have ...
... 684 - 3·210 = (sum of integers)·(110 -107)
... 54 = (sum of integers)·3 . . . . . simplify
... sum of integers = 54/3 . . . . . . divide by the coefficient of the variable
... sum of integers = 18
_____
Integers 5, 6, and 7 meet these conditions.
Quick!!! I need to do my homework
Solve: x - 1 < 3
x < 4
given x - 1 < 3 ( add 1 to both sides )
x < 4
or x ∈ ( - ∞, 4 ) ← in interval notation
help please! thanks!
Answer:
The edge length of the storage cube is 30 centimeters.
Step-by-step explanation:
All sides/edges of a cube has equal length.
Let's take the length of a edge as [tex]a[/tex] centimeters.
The volume a the cube = Height * Width * Length
All height, width and length are equal([tex]a[/tex] centimeters).
Now we can write the equation again as,
The volume a the cube = [tex]a*a*a[/tex]
Volume of the cube is given as 27,000 cubic centimeters.
Therefore,
[tex]a*a*a=27,000[/tex]
[tex]a=\sqrt[3]{27,000}[/tex]
[tex]a=30[/tex]
Therefore, the edge length of the storage cube is 30 centimeters.
Suppose the exponential regression equation for some data is y=1.923*3.772^x. When x equals 5, what is the predicted value of y? Round your anser to the nearest whole number. A. 147 B. 99 C. 992 D/ 1468
Put 5 where x is in the equation and do the arithmetic.
y = 1.923×3.772⁵ ≈ 1468.377444
The most appropriate answer is ...
... D. 1468
Answer:
the value of y when x= 5 is 1468
Step-by-step explanation:
Suppose the exponential regression equation for some data is given by y=1.923*3.772^x
We need to find out the value of y when x= 5
Plug in 5 for x and find out y
y=1.923*3.772^x
y=1.923*3.772^5=1468.37744
So the value of y when x= 5 is 1468
Evaluate the following
|10| =
|-7| =
The absolute value of a number is that number with a positive sign.
|10| = 10
|-7| = 7